2003
DOI: 10.1111/1475-4983.00317
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary morphology of oblique ribs of bivalves

Abstract: ABSTRACT. Fossil bivalves bearing oblique ribs ®rst appeared in the Mid Ordovician but their diversity remained low during the Palaeozoic. The diversity soon increased after the Early Triassic, peaking in the Early Cretaceous. The Palaeozoic±Mesozoic record is dominated by burrowing bivalves (mainly pholadomyoids and trigonioids), which developed oblique ribs with symmetric pro®les, probably adapted for shell reinforcement, although there are indications that the ribs of trigonioids also enhanced burrowing ef®… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 5 publications
0
29
0
Order By: Relevance
“…Many groups of tetrapods radiated into their main modern groups, including frogs, turtles, lizards, snakes, and birds (Benton 1996). Among marine invertebrates, speciation was particularly marked among some groups of bryozoans (Jablonski et al 1997) and a peak in bivalve diversity is also recognized (Checa & Jimenez-Jimenez 2003).…”
Section: Biotic Changesmentioning
confidence: 99%
“…Many groups of tetrapods radiated into their main modern groups, including frogs, turtles, lizards, snakes, and birds (Benton 1996). Among marine invertebrates, speciation was particularly marked among some groups of bryozoans (Jablonski et al 1997) and a peak in bivalve diversity is also recognized (Checa & Jimenez-Jimenez 2003).…”
Section: Biotic Changesmentioning
confidence: 99%
“…Veteranella reidi (Fletcher, 1945) (Permian) is the oldest species with oblique chevron-type ornamentation, which became common among bivalves during the Cenozoic, and is interpreted as an adaptation to rapid escape from potential predators and for minimizing shell damage during burrowing (Checa & Jiménez-Jiménez, 2003a). Numerous studies demonstrated that this type of ornamentation facilitates excavation (S. M. Stanley, 1969Stanley, , 1970Seilacher, 1972), so this genus is regarded as a fast burrower.…”
Section: Fang and Others 2009)mentioning
confidence: 99%
“…Features including varices, a labral tooth, an enveloped shell, and sculpture that enhances burrowing in sand are overwhelmingly tropical and warm-temperate in distribution and originated mainly during or after the Late Cretaceous (Vermeij, 2001(Vermeij, , 2005(Vermeij, , 2015Checa & Jim� enez-Jim� enez, 2003). Long-distance chemoreception, as indicated by the presence of a siphonal canal, is spatially and temporally more widespread (Vermeij, 2007), as are molluscan photosymbioses (Vermeij, 2013a), calcified opercula (Williams et al, 2008;Vermeij, 2015), and cementation and thick shells in oyster-like bivalves (Vermeij, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Vermeij, unpubl. data); photosymbiosis in bivalves, which enables faster growth and greater competitive ability (Vermeij, 2013a); burrowing-enhancing sculpture in bivalves (Checa & Jim enez-Jim enez, 2003); rigid calcareous opercula in molluscs, which deter predators from entering the aperture (Checa & Jim enez-Jim enez, 1998;Williams, Karube & Ozawa, 2008;Vermeij, 2015); overlapping shell margins, enabling bivalves to resist predatory attacks (Vermeij, 1987(Vermeij, , 2013b; and cementation and exceptional shell thickness in oyster-like bivalves (Vermeij, 1987(Vermeij, , 2014.…”
Section: Introductionmentioning
confidence: 99%